Quantum interference in grazing scattering of swift He atoms from LiF(001) surfaces: Surface eikonal approximation - Gravielle, Maria Silvia (2009)
This work deals with the interference effects recently observed in grazing collisions of few-keV atoms with insulator surfaces. The process is studied within a distorted-wave method, the surface eikonal approximation, based on the use of the eikonal wave function and involving axial channeled trajectories with different initial conditions. The theory is applied to helium atoms impinging on a LiF(001) surface along the h110i direction. The role played by the projectile polarization and the surface rumpling is investigated. We found that when both effects are included, the proposed eikonal approach provides angular projectile spectra in good agreement with the experimental findings.